Réponses

2013-03-11T12:00:26+01:00

je ne sais pas si tu as vu la formule de résolution d'une équation du second d°.

sinon:( x² - x +1/4) -5/4 = (x - 1/2)² - 5/4 = 0 => (x - 1/2)² = 5/4 =>

x - 1/2 = V5/2 ou   x -1/2 = -V5/2

x = 1/2 + V5/2  ou x = 1/2 - v5/2

  • carys
  • Modératrice confirmée
2013-03-11T12:01:40+01:00

x² - x - 1 = 0

On a le trinôme x² - x - 1 :

Δ = b² - 4ac = (-1)² - 4*1*(-1) = 1 + 4 = 5 > 0 il a a donc deux solutions

 

x1 = (-b + √Δ) / 2a = (1 + √5) / 2 ≈ 1.62

x2 = (-b - √Δ) / 2a = (1 - √5) / 2 ≈ -0.62

 

voilà :)